Modeling of Return on Pension Funds, Taking into Well-being of Older Generation; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Aksenova Y. (2017, 2017)
Title screen